Pengaruh Perbedaan Ukuran Intake Kontraksi Terhadap Laju Aliran Di Ruang Uji - Wempi Geovano Iribaram; Vina N Van Harling (Jurnal Teknik Mesin, 2023)
The contraction cone or intake is a very important part of wind tunnel design because it has a high impact on the quality of airflow in the test section. The design of the contraction cone aims to create the air pressure required at the time of entry of the test section without experiencing much turbulence. This research was conducted using an experimental method, where in this study it was carried out by testing, making 3 intake components or funnels of different sizes. The calculation results obtained funnel 1 contraction with a value of 11,466 m3 / s, funnel 2 contraction with a value of 12,266 m3 / s, and funnel 3 contraction with a value of 12,533 m3 / s. These results show that the size of the contraction affects the wind flow rate inside the test chamber. Where changes in the size of contractions will increase the wind flow rate, which is caused by the increasing size of the contraction cross-sectional area so that the shelter area or wind flow area that will move towards the test room increases in size or area